1996
DOI: 10.1212/wnl.47.4.985
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal pseudo-obstruction, myasthenia gravis, and thymoma

Abstract: Two patients presented with abdominal pain, recurrent vomiting, weight loss, and constipation secondary to intestinal pseudo-obstruction. Both patients had symptoms and signs of myasthenia gravis, acetylcholine receptor antibodies, and thymoma. In one patient inflammatory cell infiltrates and occasional degenerate neurons were found in the myenteric plexus. The gastrointestinal symptoms resolved during treatment with pyridostigmine. The close temporal relationship between the onset of the gastrointestinal symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…These myopathies or neuropathies can be either degenerative or inflammatory. Over recent years, observations have suggested that some cases of gastro-intestinal dysmotility are immune-mediated, based in part on the associations of CIPO with small-cell lung cancer and thymoma [7, 8, 14, 15], two tumours which frequently stimulate the immune system and result in paraneoplastic neurological disorders. In these cases, the antibodies detected in routine practice are often directed against intracellular antigens, such as Hu (ANNA-1), and are probably not pathogenic since there are few examples of a response to treatments that lower the antibody levels [16, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These myopathies or neuropathies can be either degenerative or inflammatory. Over recent years, observations have suggested that some cases of gastro-intestinal dysmotility are immune-mediated, based in part on the associations of CIPO with small-cell lung cancer and thymoma [7, 8, 14, 15], two tumours which frequently stimulate the immune system and result in paraneoplastic neurological disorders. In these cases, the antibodies detected in routine practice are often directed against intracellular antigens, such as Hu (ANNA-1), and are probably not pathogenic since there are few examples of a response to treatments that lower the antibody levels [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Aetiologies include disease processes localised to the colon, such as Hirschsprung’s disease, or generalised motility disorders that affect multiple regions of the gastrointestinal tract [5]. CIPO can be a paraneoplastic disorder which appears to be secondary to an autoimmune process triggered by a cross-reaction between antigens shared by the tumour cells and myenteric plexus neurons, and several cases have been reported in association with thymoma or small-cell lung cancer [6,7,8]. CIPO has also been described during the course of idiopathic autonomic neuropathy characterised by the high frequency of circulating ganglionic AChR autoantibodies [9].…”
Section: Introductionmentioning
confidence: 99%
“…In chronic EAAN, the density of neurons in paravertebral sympathetic ganglia appeared to be normal, but there was a reduction in the number of neurons in enteric plexus suggesting that some autonomic neurons not only lose synaptic nAChR but also sustain immunocytotoxic or apoptotic cell death. Inflammation and loss of ganglionic neurons have been documented in biopsied bowel of patients with paraneoplastic autoimmune autonomic neuropathy (Anderson et al 1996;Condom et al 1993;Lennon et al 1991). Enteric neurons may be particularly sensitive to an immunological attack directed against neuronal ganglionic nAChR because fast cholinergic transmission is important in both the extrinsic and intrinsic neural regulation of gut motility, and in both the motor and mechanosensory limbs of the enteric nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudo-achalasia, gastroparesis and intestinal pseudo-obstruction have all been linked to the autoantibody anti-Hu. 5,7,13,16,17 The autoantibodies found in patients with paraneoplastic GI dysmotility are different from those thought to be responsible for primary achalasia in that the former may affect neurons throughout the GI track. Therefore, many patients have a pan-dysmotility, although usually one of the above disorders will present as the predominant symptom.…”
Section: Clinical Characteristics/differential Diagnosis/serological mentioning
confidence: 99%